Probing the heme-binding site of the cytochrome c maturation protein CcmE. - Harvat, E; Redfield, C; Stevens, J; Ferguson, S (2009)
Maturation of c-type cytochromes in many bacterial species and plant mitochondria requires the participation of the heme chaperone CcmE that binds heme covalently via a His residue (H130 in Escherichia coli) before transferring it stereospecifically to the apo form of cytochromes c. Only the structure of the apo form of CcmE is known; the heme-binding site has been modeled on the surface of the protein in the vicinity of H130. We have determined the reduction potential of CcmE, which suggests that heme bound to CcmE is not as exposed to solvent as was initially thought. Alanine insertions in the vicinity of the heme-binding histidine (which we showed by NMR do not perturb the protein fold) strikingly abolish formation of both holo-CcmE and cytochrome c, whereas previously reported point mutations of residues adjacent to H130 gave only a partial attenuation. The heme iron coordinating residue Y134 proved to be strictly required for axial ligation of both ferrous and ferric heme. These results indicate the existence of a conformationally well-defined heme pocket that involves amino acids located in the proximity of H130. However, mutation of Y134 affected neither heme attachment to CcmE nor cytochrome c maturation, suggesting that heme binding and release from CcmE are hydrophobically driven and relatively indifferent to axial ligation.